Identification of IL-27 as a novel regulator of major histocompatibility complex class I and class II expression, antigen presentation, and processing in intestinal epithelial cells - Diegelmann, Julia; Brand, Stephan (Frontiers in Immunology, 2023)
Antigen presentation via major histocompatibility complex (MHC) class I and class II receptors plays a fundamental role in T cell-mediated adaptive immunity. A dysregulation of this fine-tuned recognition might result in the development of autoimmune diseases such as inflammatory bowel diseases that are characterized by chronic relapsing inflammation of the intestinal tract and a damaged intestinal epithelial barrier. While MHCII receptors are usually expressed by professional antigen presenting cells (APC) only, there is increasing evidence that non-immune cells such as intestinal epithelial cells (IEC) might express MHCII upon stimulation with IFN-γ and thus act as non-professional APC. However, little is known about other factors regulating intestinal epithelial MHC expression. Here we identify IL-27 as an inducer of different MHCI and MHCII receptor subtypes and the invariant chain (CD74/li) in IEC via the STAT1/IRF1/CIITA axis. CIITA, MHCII and CD74 expression was significantly increased in IEC from Crohn’s disease (CD) patients with active disease compared to controls or CD patients in remission. IEC phagocytosed and digested external antigens and apoptotic cells. IL-27 strongly stimulated antigen processing via the immunoproteasome in a IRF1-dependent manner. In co-culture experiments, antigen-primed IEC strongly enhanced lymphocyte proliferation and IL-2 secretion, dependent on direct cell-cell contact. IL-27 pretreatment of IEC significantly reduced IL-2 levels in lymphocytes in co-culture. In summary, we identified IL-27 as a novel regulator of IEC antigen processing and presentation via MHCI and MHCII receptors, underscoring the importance of IEC as non-professional APC.